Revisiting Ricardo: Can productivity differences explain the pattern of trade between EU countries? - Michel Beine (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
In this paper we revise the empirical tests of the Ricardian model by testing properly the Ricardian hypotheses on bilateral trade flows. Our tests are based on NACE 2-digit industry aggregation of productivity and of bilateral trade flows between 21 EU member states for the period 1994-2004. We compare the matchings between relative bilateral sectoral productivity rankings and bilateral sectoral exports-to-imports ratio rankings for each of 21 x 20 country pairs. We find that the Ricardian hypothesis is surprisingly good at predicting the static pattern of bilateral trade between individual EU member states even after controlling for the Heckscher-Ohlin type of capital-to-labor ratios. Long-tfirm changes in the bilateral trade patterns, however, do not seem to be explained consistently neither by the variation in changes of relative productivity nor by the variation in changes of capital-to-labor ratios. Furthfirmore, we find quite a strong autoregressive impact of initial trade patterns on the long-tfirm comparative advantages in the bilateral trade among countries. This implies that comparative advantages are structural by nature and that Ricardian differences in relative productivity can account for a good part of their static representation. Explaining their dynamic evolution over time, however, requires further research.
Keywords: D24; F14; 330; international trade; productivity; Ricardian hypothesis; empirical tests; Außenhandelsstruktur; Komparativer Kostenvorteil; Produktivität; EU-Staaten